The Role of Corporate Communication in Image Penetration through Podcast Media - Astaria, Mia; Ruliana, Poppy (Jayapangus Press, 2024)
In the era of society 5.0, Indonesia and the world are experiencing developments in all fields, especially technology, information, and global competition. It takes hard work from the corporate communication division so that the company has a clear identity that can make it different from similar companies in order to form a good image that stands out. The purpose of this research is to represent BRI's Corporate Communication strategy in shaping its image through podcast media. This research is a descriptive qualitative research with data collection techniques conducted through structured interviews, with guidelines for conducting research virtually through Google Meet, Zoom or Video call and WhatsApp text connection. In selecting informants using purposive sampling technique in determining research subjects. The research instrument used is a list of questions and data analysis techniques using open coding to selective coding which will draw conclusions from these results. In planning a Corporate Communication activity, the author also uses the RACE model from John Marston. The results showed that the penetration of BRI's new image through the BRI Office Break podcast program broadcast on Youtube was considered quite successful. The conclusion of this research: up to the 10th episode of the BRI Office Break Podcast has successfully portrayed BRI's new image, customers and non-customers view BRI as a sophisticated and modern bank, no longer old-fashioned or conventional.